If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -12p = 8 Combine like terms: p + -12p = -11p -11p = 8 Solving -11p = 8 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-11'. p = -0.7272727273 Simplifying p = -0.7272727273
| 4-(x-6)=15 | | -24=56-8y | | 8-13(-4)= | | 4x*-196=0 | | 4(4x-8)+11x= | | 12x+36y-96=75 | | c+17c=7 | | 3x-18=23 | | f(x)=21+5.50x | | -7x=700 | | 3/4x-7/25/6 | | 14x+5y=20 | | x*-343=0 | | 6=(2)4-5 | | 6(x+5)-7=2x+4(5+x) | | 6x^2-9=4x^2+2x-6 | | 2(-1-m)=2(3) | | x=6/x=10/7 | | 61e+24=93e | | 15-(6-2y)=3y+9 | | 2-0.2= | | 12.89=8C*B | | X=-11/5 | | 10+2x=7z | | 23x+61=19x+73 | | -1(x+4)=2x+35 | | 3.6x+.7=-1.4x+3.2 | | 5(a+1)= | | 7.8x-2.3=2.8x+7.7 | | Y=.11x+18.82 | | 2x=1/2(20) | | 6x+5cos(x)-4=0 |